Pengaturan Kecepatan Dan Pengendalian Motor DC 5 V-110 V Menggunakan IC Tipe NE 555 - Anwar, Nur Effendi; Ferdilla, Helga (Jurnal Teknologi Riset Terapan, 2023)
Purpose: To determine the regulation of the rotation speed of a DC motor using an NE 555 type IC and by providing a stable voltage with the same working frequency but varying DC motor speed control pulse cycles. Methodology: This research method includes several stages, the stages in the research are as follows: The data required is the specifications of each component and the specifications of the hardware design to be made. The selection of tools and materials used must be in accordance with what is expected for setting and controlling the speed of a DC motor Result: The effect of the armature current (Ia) on the rotation speed of the motor is directly proportional; that is, the greater the rotation speed of the series self-amplifying DC motor. Conclusion: DC motor speed increases with Va and Ia. IC NE555 enables simple, affordable PWM control, though manual potentiometer adjustment lacks precision. Limitations: Dependence on specific ICs: Focusing on the use of the NE 555 IC may limit the understanding of other alternatives that may be more suitable or efficient for certain applications. This article could be better if it includes a comparison with other available methods or ICs. Contribution: This study can provide practical insight into how to implement DC motor speed adjustment in various applications, such as in the fields of automation, robotics, and other small control systems. This may help readers who wish to apply the techniques taught in their projects.